Low Chirp EMLs Fabricated By Combining SAG and Double Stack Active Layer Techniques - Qiufang Deng; Hongliang Zhu; Xiao Xie; Lu Guo; Siwei Sun; Song Liang; Wei Wang (IEEE Photonics Journal, 2018)
We present electroabsorption modulators integrated with distributed feedback lasers (EMLs) fabricated by a simple method, which combines the advantages of the selective area growth and double stack active layer techniques. The obtained EML device has a threshold current as low as 16 mA and optical power of larger than 10 mW at 85 mA laser current. Quite low chirp parameter of the fabricated EMLs is obtained. Negative chirp parameters can be obtained at only about 0.5 V reverse bias voltage. Open eye diagrams are demonstrated from the EML at both 10 and 20 Gb/s modulations with the driving voltage of only 0.65 V while securing high dynamic extinction ratio. The exhibited performance makes our device a very promising candidate as a simple light source in long distance and cost sensitive applications.